2006
DOI: 10.1016/j.jinorgbio.2005.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative dealkylation DNA repair mediated by the mononuclear non-heme iron AlkB proteins

Abstract: DNA can be damaged by various intracellular and environmental alkylating agents to produce alkylation base lesions. These base damages, if not repaired promptly, may cause genetic changes that lead to diseases such as cancer. Recently, it was discovered that some of the alkylation DNA base damage can be directly removed by a family of proteins called the AlkB proteins that utilize a mononuclear non-heme iron(II) and α-ketoglutarate as cofactor and cosubstrate. These proteins activate dioxygen and perform an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 86 publications
(175 reference statements)
1
72
0
Order By: Relevance
“…More recently, ALKB has been found to be highly conserved in various species, and currently there are eight homologs in human cells, including ALKBH5 (hABH5) (32)(33)(34). Although all hABH proteins share sequence similarities with bacterial ALKB, only hABH2 and hABH3 have DNA repair functions and catalyze oxidative demethylation in the presence of Fe(II) and ␣-ketoglutarate.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, ALKB has been found to be highly conserved in various species, and currently there are eight homologs in human cells, including ALKBH5 (hABH5) (32)(33)(34). Although all hABH proteins share sequence similarities with bacterial ALKB, only hABH2 and hABH3 have DNA repair functions and catalyze oxidative demethylation in the presence of Fe(II) and ␣-ketoglutarate.…”
Section: Discussionmentioning
confidence: 99%
“…64,65 Non-heme iron enzymes participate in oxidative Ndealkylationreactionsinnature,andhigh-valentiron(IV)-oxo species have been invoked as an active oxidant that effects the oxygenation of organic substrates. 66 We , N-methylaniline was produced as a major product with the concurrent formation of CH 2 O. 26 Detailed mechanistic studies were carried out in an effort to understand whether the oxidative N-dealkylation occurs via an electron transfer-proton transfer (ET-PT) mechanism or a hydrogen atom transfer (HAT) (Scheme 8).…”
Section: High-valent Iron(iv)-oxo Complexes Nammentioning
confidence: 99%
“…34 Nonheme iron(IV) oxo complexes have also been shown to effect oxidative N-dealkylation, a reaction recognized in nature for nonheme iron enzymes. 43 Mechanistic studies on the reaction of synthetic models with N,N-dimethylaniline demonstrated that rather than HAT the reaction proceeds via electron transfer followed by proton transfer. 40 Finally, nonheme iron(IV) oxo species undergo complete intermetallic OAT to Fe II .…”
Section: Oat With Nonheme Ironmentioning
confidence: 99%